Reconstruction of lost and incomplete historical texts, from the fifth to the fourteenth century AH/tenth to twentieth century AD: selected models - Al-Leheabi, Saleh (Al-Adab Journal, 2025)
The historical library is rich in many manuscripts and printed sources that provide specialists and researchers with the scientific content necessary to study and understand the historical course of events and build important historical information in its field. However, we find that many sources lack perfection and are affected by deficiency and loss; for several reasons, including material, human, natural, intentional, and others; which constitutes a severe deficiency in these sources and in the importance, nature, perfection, and completeness of the scientific material they provide, and thus disrupts the scientific value of these sources and the extent of their benefit, which may lead to abandoning them. We also find mention of some books and publications, but they were lost over time and their texts were scattered in the books, which necessitates re-collecting them again and presenting them to students in the form of a single source as it was in its original form, or at least in the closest image to the lost original. This is undoubtedly a difficult task and requires great and exceptional effort with great knowledge, awareness, and comprehension in this field, which not every researcher and historian is proficient in, but rather it is the work of historians and investigators experienced in their field of specialization. The most prominent objectives of the research are: identifying the reasons for the loss and deficiency in the original historical sources, what led to this, how to re-collect the missing texts and reconstruct the texts, and complete the deficiency and missing parts of these original sources, and clarify how to use scientific methods and methodology that contribute to restoring these texts to their correct status and reusing and employing them in historical studies. The desired results of the research include: providing a mechanism and methodology for how to deal with historical sources and texts that are missing or parts of which are missing, and how to benefit from them, as well as encouraging researchers to work and practice this type of purposeful and promising scientific research, with tracking down the sources that are still missing and how to work on serving them in the required scientific manner.